2008
DOI: 10.1542/peds.2007-3027
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Medical Outcomes of Early Newborn Screening Programs for Phenylketonuria

Abstract: We found little evidence of death or disability that resulted from the inappropriate treatment of well children who were falsely identified by early newborn screening programs. Because the first decade of newborn screening typically reveals diagnostic and therapeutic complexity, systematic follow-up of screened populations and rapid dissemination of results may reduce morbidity/mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…30 Norman Fost claims that these errors in PKU testing caused brain damage and even death in some infants; 31 however, a subsequent study conducted found that there was insufficient evidence of such harm. 32 Importantly, modern rapid turnaround time for lab results, significant advances in the field of metabolic nutrition, and improved understanding about human metabolism together reduce the risk of potential harm from erroneous over-treatment for diseases like PKU. Despite this progress, there will continue to be risk involved in screening for new diseases where the phenotypic spectrum is not fully understood prior to the onset of screening.…”
Section: Ethical Concernsmentioning
confidence: 99%
“…30 Norman Fost claims that these errors in PKU testing caused brain damage and even death in some infants; 31 however, a subsequent study conducted found that there was insufficient evidence of such harm. 32 Importantly, modern rapid turnaround time for lab results, significant advances in the field of metabolic nutrition, and improved understanding about human metabolism together reduce the risk of potential harm from erroneous over-treatment for diseases like PKU. Despite this progress, there will continue to be risk involved in screening for new diseases where the phenotypic spectrum is not fully understood prior to the onset of screening.…”
Section: Ethical Concernsmentioning
confidence: 99%
“…Brase criticised the PKU test: ‘While the test has been beneficial to many babies, it has also caused devastating harm to other children, including nutritional deficiencies, death, and an increase in the number of children with mental retardation’ 19. Paediatric bioethicist Norman Fost proposed that the inaccuracy of the PKU test led to death and disability in a large number of children who otherwise would have been healthy,20 but a 2008 study published in Pediatrics found little evidence of such harm 21. Brase expressed the opinion, in need of further evidence, that a disproportionate number of infants developed mental retardation and disability due to test inaccuracy and maternal PKU syndrome 19.…”
Section: Criticism and Backlashmentioning
confidence: 99%
“…Ultimately, a number of cases may be found to be false positive, causing increased parental stress and perturbed parental bonding and overreaction in the future [13] . When newborn screening for PKU was introduced, some infants with false-positive screening results were started on a phenylalanine-restricted diet, but apparently did not suffer from any adverse outcomes [14] . Although the number of disorders that are screened for vary from country to country, PKU is included in most if not all screening programs around the world [6,7] .…”
Section: Newborn Screening -Principles and General Commentsmentioning
confidence: 99%